Kos ekonomi penyalahgunaan dadah - Ali, Jamal; Hassan, Sallahuddin; Abdul Karim, Noor Al-Huda (Agensi Antidadah Kebangsaan, 2010)
High level of drug abuse increases drug related diseases, violence and crimes, productivity losses and collapse in social structure and economy. Thus, drug abuse significantly poses health care cost, crime career cost, productivity losses and other drug related costs. This study attempts to measure economic costs of drug addiction and abuse in Malaysia in Ringgit Malaysia amounts. The estimated costs cover the total health care cost for each drug abuse, crime career cost, losses of income, productivity losses, and the government agencies and non-government organization expenditure for enforcement and rehabilitation activities. Based on the findings from this study, the total cost of existing enforcement and rehabilitation related to drug abuse was estimated at RM177 million in 2008. Meanwhile, the health care cost, productivity losses, crime career cost, and other indirect costs for 63,884 drug addicted in Malaysia were estimated at RM8.47 billion. Finally, all the direct and indirect economic costs of illicit drugs were estimated at RM8.65 billion, representing RM332 per capita.